Application of hybrid evolutionary algorithm (HEA) to discover the best rule set to explain dissolved oxygen (D.O.) dynamics in 2 freshwater lakes / Awanis Azizan - Awanis, Azizan (2012)
This project was initiated to study the ability of Hybrid Evolutionary Algorithms (HEA) in predicting the best rule sets to explain the dynamics of dissolved oxygen pattern in 2 freshwater lakes, Tasik Bera (Bera Lake) and Putrajaya Lake. In this study, we would like to observe the correlation between dissolved oxygen and other water quality parameters of the respected lakes that have been generated by the training of the algorithm. After each data training, analysis on rule sets generated was done and comparison was made against a set of testing data. Relations between each parameter were individually examined on how they reflect to the dynamics of oxygen concentration in the water bodies. The result obtained is compared to the existing research or literature to support the findings.